Biofilm formation and role of other pathogenic factors in the virulence of Staphylococcus epidermidis clinical isolates - María Coronada Fernández-Calderón; María Coronada Fernández-Calderón; María Coronada Fernández-Calderón; Irene Fernández-Babiano; Irene Fernández-Babiano; María Luisa Navarro-Pérez; Carmen Pazos-Pacheco; Carmen Pazos-Pacheco; Antonia Calvo-Cano; Antonia Calvo-Cano; Antonia Calvo-Cano (Frontiers in Cellular and Infection Microbiology)
Medical device-associated infections represent a significant healthcare challenge, as sterilization of the biomaterial often necessitates device removal. The most frequently isolated microorganism in these infections is Staphylococcus epidermidis, a skin commensal capable of causing a wide range of nosocomial infections. The primary virulence factor of S. epidermidis is biofilm formation, which decreases antibiotic efficacy and host immune response. However, additional factors play crucial roles in infection establishment. Understanding the interplay between virulence factors is essential to developing preventive strategies that inhibit microbial adhesion and biofilm development. In this study, we analyzed the presence of genes associated with adhesion and biofilm formation (ica-dependent and ica-independent pathways) in 25 clinical isolates of S. epidermidis and four control strains: ATCC 12228, ATCC 35983, ATCC 35984, and the HAM 892 mutant. Resistance profile was determined, and biofilm quantification and composition of matrix was performed using multiple methodologies. Additionally, parameters associated with initial adherence as cell surface hydrophobicity (CSH) were investigated. A strong correlation was observed among different methods for measuring biofilm formation and matrix composition. The 14 icaADBC+ isolates exhibited higher prevalence of the aap, bhp, mecA, and IS256 genes, with polysaccharide intercellular adhesin (PIA) identified as the main matrix component. In contrast, icaADBC− biofilm-producing strains formed biofilms rich in other polysaccharides and proteins. The 15 non-biofilm-producing isolates showed significantly higher hydrophobicity levels, suggesting that this factor plays a critical role in initial adhesion and colonization. This study highlights the diverse mechanisms underlying biofilm formation in S. epidermidis and identifies hydrophobicity as a potential pathogenicity factor contributing to its virulence.